Development of bubble absorption refrigeration technology: A review. (February 2018) - Wu, Xi; Xu, Shiming; Jiang, Mengnan
Abstract: This study reviews the developments of bubble absorption refrigeration technologies. Firstly, the principles of the bubble absorption refrigeration systems as well as bubble absorbers were introduced; And then bubble behavior characteristics during the absorption process were observed and expressed graphically; Thirdly, available bubble absorbers were investigated, modeled and compared; In addition, current and potential refrigerant-absorbent pairs in the bubble absorption refrigeration systems were analyzed, and about fifty fluids were involved totally. What's more, methods of enhancing bubble absorption performance were researched, and also the influence mechanisms of these physical and chemical methods were explained; Finally, the development of bubble absorption refrigeration technologies were discussed from the aspects of driving energies, performance enhancement and application extension. The tendency of bubble absorption refrigeration technologies is expected to be high efficiency, miniaturization, and intellectualization. The expressed contents in this paper are expected to be useful for readers in the fields of absorption refrigeration technologies and the medium-low grade heat utilization technologies, especially for the equipment operating in the unsteady conditions (e.g. swing, bump, jolt, scram, etc.). Graphical abstract: fx1